Pengaruh Gaya Kepemimpinan Dan Pelatihan Terhadap Kinerja Karyawan PT Garda Paksi Nusantara Di Jakarta Selatan - Azriel Wicaksono; Ibnu Sina (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to examine the effects of training and leadership style on employee performance at PT Garda Paksi Nusantara, both partially and simultaneously. It uses a quantitative, associative approach with data processed using SPSS version 23. The population and sample consisted of 55 employees from PT Garda Paksi Nusantara Jakarta. Data analysis included instrument testing, classical assumption testing, regression analysis, correlation, determination coefficients, and hypothesis testing. Leadership style also has a positive and significant partial effect, with a t-value of 4.589 above 2.00665 and a significance level of 28.4%. Therefore, the null hypothesis is rejected. The results show that training has a positive and significant partial effect on employee performance, with a t-value of 6.210 exceeding the table value of 2.00665 and a significance level of 42.1%. Thus, the null hypothesis is rejected. Simultaneously, leadership style training significantly influence employee performance, shown by the regression equation: Y = 19.891 + 0.574 X1 + 0.026 X2. The F-value of 18.961 exceeds the table value of 3.18, with a significance level of 42.2%.